2014
DOI: 10.1158/0008-5472.can-14-0197
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Discovery of a Novel Class of Cinnamic Hydroxamates as Histone Deacetylase Inhibitors by Multimodality Molecular Imaging in Living Subjects

Abstract: Histone deacetylases (HDAC) that regulate gene expression are being explored as cancer therapeutic targets. In this study, we focused on HDAC6 based on its ability to inhibit cancerous Hsp90 chaperone activities by disrupting Hsp90/p23 interactions. To identify novel HDAC6 inhibitors, we used a dual-luciferase reporter system in cell culture and living mice by bioluminescence imaging (BLI). On the basis of existing knowledge, a library of hydrazone compounds was generated for screening by coupling cinnamic hyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Similarly, vorinostat was used at a concentration of 150 mg/kg in urothelial carcinoma . Several other newer HDAC inhibitors have also been evaluated in vivo in various cancer models. In the case of in vivo evaluation of PPARγ agonists in various cancer models, a similar trend is observed. Hence, dual-targeting compound 7c with %TGI of 24% appears more potent than single-targeted agents. Considering its in vivo efficacy at higher doses, 7c analogues and other HDAC inhibitors or PPARγ agonists might be used as an adjuvant to existing chemotherapy to help reduce resistance/toxicity issues and possibly enhance antitumor effects in a synergistic manner.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Similarly, vorinostat was used at a concentration of 150 mg/kg in urothelial carcinoma . Several other newer HDAC inhibitors have also been evaluated in vivo in various cancer models. In the case of in vivo evaluation of PPARγ agonists in various cancer models, a similar trend is observed. Hence, dual-targeting compound 7c with %TGI of 24% appears more potent than single-targeted agents. Considering its in vivo efficacy at higher doses, 7c analogues and other HDAC inhibitors or PPARγ agonists might be used as an adjuvant to existing chemotherapy to help reduce resistance/toxicity issues and possibly enhance antitumor effects in a synergistic manner.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Our data showed that GGD inhibited HDAC6 and increased tubulin acetylation, which may have beneficial effects on heart failure. These effects are consisted with one report that cinnamic acid, one of the major constituents of Cinnamomum cassia Presl., inhibited HDAC activity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HDAC inhibitor BAS-2 inhibits HDAC6, affects the ENO1 gene and LDHA related to glucose metabolism, and ultimately affects glycolysis in breast cancer (Dowling et al, 2021). Studies have shown that 1A12 can inhibit the acetylation level of histone H3, and it can also affect the glucose metabolism level in preclinical test subjects (Chan et al, 2014). HDAC inhibitors (panobinostat, vorinostat, and romidepsin) reduce glycolysis in a c-MYC-dependent manner, triggering the metabolic reprogramming of glioblastoma (Nguyen et al, 2020).…”
Section: Clinical Trialsmentioning
confidence: 99%